PENGARUH PENGGUNAAN MEDIA SOSIAL SELAMA STUDY FROM HOME TERHADAP MOTIVASI BELAJAR DAN DISIPLIN BELAJAR (STUDI KASUS PADA MAHASISWA PENGGUNA AKTIF MEDIA SOSIAL SELAMA STUDY FROM HOME) - Lathifa Nourthalia Putri; Antyo Pracoyo (Journal of Accounting, Management and Islamic Economics, 2024)
This study aims the influence of social media, study from home, learning motivation, and learning dicipline on the college students who is actively using social media during study from home in South Jakarta. The independent variables in this study are Social Media and Study From Home. While, the dependent variables in study are Learning Motivation and Learning Dicipline. Hypothesis in this study uses the SEM (Structural Equation Modeling) method, which is supported by SmartPLS 3.2.9 and IBM SPSS Statistics 26 application devices. The data collection technique in this study used an online questionnaire with the Google Form application to collect the respondents’ informations, who were a college students who is actively using social media during study from home in South Jakarta. The results of this study indicate that: 1) Social Media has a positive and significant effect on Study From Home; 2) Study From Home does not have an effect on Learning Motivation; 3) Study From Home does not have an effect on Learning Dicipline.